Influence Of Parents And Peers On Internet Usage And Addiction Amongst School-Going Youths In Malaysia - Hooi, Patrick Soh Chin (2010)
The purpose of this thesis is to study the motives of internet usage among school-going youths in Malaysia and the impact on Internet addiction by the motives, as well as the influence by parents and peers.